Standar Prosedur Operasional (SPO) pada proses produksi pengolahan rumput laut menjadi tepung di PT Bantimurung Indah Kabupaten Maros - Adnan Engelen (Journal Of Agritech Science (JASc), 2017)
Standard Procedure Operational (SOP) is organizational activator mechanism can walk effectively and efficient. This research aim to to get and apply obtained SOP in each step process processing of sea grass become flour. Beautiful PT Bantimurung of Sub-Province of Maros. Not yet been known by process step him able to bother applying of SOP, like if natural water rate of degradation and at drier process do not get rate irrigate 13% because influenced by season and climate. Hence needed by research with aim to study process processing of grass go out to sea so that can apply standard standard and written able to be used in course of processing of sea grass become flour so that get procedure or decision of activity to making of sea grass flour semi of carragenan refined good so that obtain, get result matching with consumer appetite. If SOP do not be applied by hence will incidence of less good best quality to product as well as the happening of variation quality of inexistence effect applying of SOP. Method used at this research is field survey, making of kusioner, interview,processing and presentation of data. From this research have got SOP processing of sea grass become flour at steps like wash, poaching, amputation, draining, flour and sortasi is so that got by quality of processing result by kontinu.